Performance-based engineering: formulating sustainable concrete with sawdust and steel fiber for superior mechanical properties - Waqar, Ahsan; Khan, Muhammad Basit; Najeh, Taoufik; Almujibah, Hamad R.; Benjeddou, Omrane (Frontiers in Materials, 2024)
Construction using eco-friendly materials reduces environmental impact and promotes sustainable practices. This research uses sawdust and steel fibers to design sustainable concrete. The main goal is to improve mechanical properties and reduce embodied carbon emissions. This study examines the mechanical properties of concrete with different sawdust and steel fiber combinations to fill a gap in the literature. In this research synergistic effect of saw dust and steel fiber on concrete characteristics have been studied. The research also examines these pairings' environmental benefits. This study used a response surface methodology (RSM) to design an experimental program and assess the effects of input variables (sawdust and steel fiber percentages) on output responses like compressive strength (CS), split tensile strength (STS), flexural strength (FS), modulus of elasticity (MOE), embodied carbon (EC), and eco-strength efficiency (ESE). Established testing methodologies and RSM provided an optimum prediction model based on specimen mechanical properties. Sawdust and steel fibers enhances concrete's mechanical properties. Varying proportions of both materials were added in mix; sawdust (0-12%) and steel fiber (0-2%). The experimental findings suggest that the optimized composition achieved the following mechanical properties: 13.85 MPa compressive strength, 1.4 MPa split tensile strength, 3.67 MPa flexural strength, 18.027 GPa modulus of elasticity, 211.272 kg CO2e/m3 embodied carbon, and 0.065487 eco-strength efficiency. This research showed that the aims of improving mechanical properties and reducing embodied carbon were achieved. As per multiobjective optimization, optimal percentages of saw dust and steel fibers in concrete are 11.81% and 0.063% respectively. The investigation yielded many suggestions. To test the optimal blend composition of ecologically friendly concrete in real-world building projects, start with realistic projects. Finally, life cycle evaluations and cost studies are needed to determine the environmental and economic impacts of eco-friendly concrete compared to standard options.